Bridging Social and Structural Factors in Addressing Firearm Mortality: A PMESII-informed Approach - Gbadebo, Michael Olayinka; Gbadebo, Oluwafemi Adeola (Asian Journal of Advanced Research and Reports, 2025)
This study investigates the social and infrastructural determinants of firearm violence in the United States through a PMESII-informed analytical framework. Drawing from open-access national datasets, including CDC WISQARS, the American Community Survey, County Health Rankings & Roadmaps, and the CDC/ATSDR Social Vulnerability Index, the research analyzes data from 2,914 U.S. counties. Employing multivariate linear regression, principal component analysis with clustering, and interaction term modeling, the study evaluates how systemic variables contribute to firearm homicide rates. The findings highlight that higher educational attainment (β = -0.176, p < .001) and stricter gun laws (β = -0.045, p < .001) are the most significant protective factors. Furthermore, infrastructural strength measured through healthcare access, housing quality, digital connectivity, and civic support shows a strong inverse correlation with firearm mortality. Notably, a compounded risk effect (β = 3.303, p < .001) emerges in counties with both high social vulnerability and weak infrastructure, underscoring the need for integrated interventions. The study advocates for targeted policy reforms that strengthen educational equity, enforce robust firearm regulations, and expand infrastructure in high-risk areas. These findings emphasize the critical importance of multi-dimensional, data-driven strategies in mitigating gun violence and offer an actionable framework for researchers, policymakers, and urban planners addressing public safety through systemic resilience.